The Influence of Work Ethic, Intrinsic Motivation, and Job Satisfaction on Employee Performance (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This study aims to analyze the influence of work ethic, intrinsic motivation, and job satisfaction on employee performance in companies operating in the city of Cirebon. Employee performance is a crucial indicator in ensuring the sustainability and competitiveness of a company. However, a mismatch between the potential of human resources and actual outcomes in the field still frequently occurs, as evidenced by low productivity, high turnover rates, and weak employee loyalty. This research offers novelty by simultaneously examining the three internal psychological variables within a single research model, which differs from previous studies that tested them partially. The research method employed is quantitative with an associative causal design. Data were collected through Likert-scale questionnaires distributed to 50 respondents using purposive sampling. The analysis was conducted using multiple linear regression with the help of SPSS version 25 to measure the effect of each independent variable on the dependent variable, both partially and simultaneously. The findings indicate that work ethic, intrinsic motivation, and job satisfaction significantly affect employee performance. Work ethic has a positive relationship, intrinsic motivation shows a negative effect when not aligned with organizational support, and job satisfaction contributes to creating psychological comfort and employee loyalty. Simultaneously, these three variables explain a significant proportion of performance variation. This study implies that companies need to develop human resource management strategies that not only focus on technical aspects but also on strengthening the psychological factors of employees in a comprehensive manner.